An Analysis of a Traumatic Narrative in Zora Neale Hurston’s Barracoon: The Story of the Last “Black Cargo” - DJOSSOU AGBOADANNON, Koumagnon Alfred; GBAGUIDI, CELESTIN (My University, 2022)
This essay analyses the recurring debate around the trauma resulting from the Trans-Atlantic slave trade through the account of the last enslaved, Oluale Kossola, in Zora Neale Hurston’s Barracoon (2018). It tracks the long itinerary taken by the evil caravans as revealed in Kossola’s testimony and demonstrates the active participation of African peers and monarchs in the trade that took place for years and resulted in millions of deported. The Atlantic slave trade organized to that scale was particularly mischievous with long-standing consequences on the economy, demography and politics of the African states which organized or underwent it. Naturally and innately resilient, exiled like Kossola created and found ways to keep on surface culturally and emotionally, a resiliency that enabled all the enslaved population of Africatown to survive and create a new life, a new Africa out of their psychological and physical distress. Using Fanon’s psychoanalysis and Caruth’s new historicism to examine Kossola’s mental suffering from loss, grief and loneliness in the New World, the essay unearths the wounds, horrors and the pain of his kidnapping and capture from Africa as is mapped in Barracoon, before suggesting some possibilities of compensation.
Keywords: Trans-Atlantic; trade; slave; narrative; trauma; memory.